Prêmio salarial do setor público no Brasil: uma análise de equilíbrio geral dinâmico e estocástico - Paula, Guilherme Cemin de (2017)
In this dissertation I studied the two dynamic stochastic general equilibrium (DSGE) models available in the literature designed to study the dynamics of the public sector wage premium [(CÓRDOBA; PÉREZ; TORRES, 2009),(VASILEV, 2013)], calibrating them for the Brazilian economy, based on data from 2002 to 2014. In addition to performing simulations in the impulse response context, I analyzed the goodness of ﬁt of each model, comparingthetheoreticalsecondmomentsofthesimulateddataserieswiththeirempirical counterparts. The Vasilev model proved to be superior in this analysis. The exceptions are related to the underestimation of the volatility of the labor input by the two models, which can be partially explained by the fact that the labor are designed to be homogenous.